Virtual simulation of mass casualty drills: using breakout rooms to simulate physical locations - Padaki, Amit S.; Rudner, Joshua R.; Phillips, Lara L. (Frontiers in Disaster and Emergency Medicine, 2024)
The spread of COVID-19 has posed a significant challenge to educators in the disaster medicine community. While lectures can often be given remotely with little revision, simulations and other workshops can prove more challenging to adapt. Here, we describe our framework for conducting multi-site mass casualty simulations via video conference.The authors of this paper adapted a mass casualty scenario from an in-person format to a virtual format delivered via the video conference software Zoom. Key physical locations of the simulated incident were mapped onto separate video conference breakout rooms. With this geographic framework established, rules were created to govern movement, communication, treatment, and transportation.Results: Three separate virtual MCI drills were conducted. Both students and instructors were able to grasp the new format quickly. Students reported the drills to be informative and engaging, and instructors felt the drills mimicked the real-world experience well. This format had the added benefit of allowing multiple rounds of simulation to occur in rapid succession.Discussion: Using breakout rooms to simulate physical locations can be a simple and intuitive framework for adapting disaster scenarios for remote delivery. We believe other instructors can utilize this framework to increase the availability of their educational content.